CHILDREN'S TOOTHPASTE EFFECT CONTAINED FLUORIDE AND XYLITOL ON MICRO HARDNESS OF PRIMARY TEETH ENAMEL IN VITRO (PENGARUH PASTA GIGI ANAK YANG MENGANDUNG FLUORIDE DAN XYLITOL TERHADAP KEKERASAN MIKRO ENAMEL GIGI ANAK SECARA IN VITRO) - Henri Hartman; Badi Soerachman; Imanda Asysyifa Salma (Journal of Health and Dental Sciences, 2022)
Children's toothpaste has a variegated of ingredients. Each ingredient has different benefits, one of which is to increase the hardness of tooth enamel. Several factors could affect the hardness of tooth enamel, such as fluoride and Xylitol. This study aimed to determine the effect of children's toothpaste containing fluoride and Xylitol on the micro-hardness of children's tooth enamel. The research method used a laboratory experiment measuring the micro hardness of primary tooth enamel before and after treatment using the Vickers Hardness Tester. The samples were treated on primary incisors and divided into two groups, first as the experiment group and another one as the control group. The treatment was carried out using two types of children's toothpaste containing fluoride and Xylitol. After the final measurement, the data were analyzed using the Independent T-test (p <0.05), which was previously tested for normality and homogeneity with Shapiro Wilk (p <0.05) and Levene's test (p <0.05). The results showed that the sample group that was treated with toothpaste containing fluoride and Xylitol experienced an increase in the microhardness of the enamel differences. The results of data analysis with the Independent T-Test showed p = 0,02 (p<0,05) in the fluoride group, indicating that there was a significant increase, and the results in the xylitol group p = 0,003 (p<0,05). These results suggest that toothpaste containing fluoride and Xylitol can affect the microhardness of children's tooth enamel. The research concluded that children's toothpaste containing fluoride and Xylitol could be a tool to prevent dental caries because it can increase the micro hardness of tooth enamel. DOI : 10.54052/jhds.sd22.p153-168